Contact-induced stiffening in ultrathin amorphous polystyrene films. (26th September 2018) - Liu, Hao; Liu, Wentao; Fujie, Toshinori; Nakajima, Ken
Abstract: Ultrathin polystyrene (PS) films ranging from 14 nm to 316 nm were measured by atomic force microscopy (AFM) based nanomechanical mapping. Both supported and freestanding films were investigated to estimate the possible effect of the substrate. The as prepared supported ultrathin PS films show evident increase of Young's moduli and heterogeneities when the film thickness is reduced to less than 40 nm, whereas no clear thickness dependence can be found for ultrathin films after annealing. Besides, as prepared freestanding PS films thinner than 40 nm also show increased Young's moduli as decrease of the film thickness. The observed increased Young's moduli could be associated with the nano-confined film and contact load of the hard cantilever probe, where the adjacent molecular chains are perturbed and form a mechanically confined phase at the probe/polymer interface. Moreover, since as prepared and annealed ultrathin PS films show different thickness dependence in Young's moduli, it implies residual stress, confinement state of polymer chains, chain conformation, etc., which can be changed by annealing, affect the observed contact stiffening. Graphical abstract: Image Highlights: Contact-induced stiffening of ultrathin PS films is found and investigated by AFM. The ultrathin PS films show an evident increase in heterogeneity. The stiffening is independent of whether the films are supported or freestanding. Annealing has a significant effect on the Young's moduli of ultrathin PS films.